SOSIALISASI AMAN BERMEDIA SOSIAL DI ERA DIGITAL AGAR TERHINDAR DARI KEJAHATAN SIBER BAGI SISWA/SISWI SMA NEGERI 13 MAROS - Alwi, Erick Irawadi; Hasanuddin, Tasrif (LPPM Institut Pendidikan Nusantara Global, 2022)
Students to become the next generation for the nation and state must have knowledge of how to use technology properly. Not all students have an understanding of how to socialize safely in order to avoid cyber crimes which will become increasingly massive in the future, and students from SMA Negeri 13 Maros are no exception. For this reason, socialization and training on safe social media are needed so that students at SMA Negeri 13 Maros can avoid cyber crimes such as theft of personal data, fraud on behalf of other people on social media, cyber bullying to breaking into other people's accounts. The method used in this service is in the form of socialization and training in providing education to students of SMA Negeri 13 Maros. To measure the level of understanding before socialization, a pre-test was carried out with a result of 36.6 and a post-test after socialization of 85.8. From these results, it can be concluded that community service activities have increased partners' understanding regarding safe social media to avoid cyber crime.